O GeoGebra Classroom e o estudo de funções: contribuições para o desenvolvimento do pensamento algébrico - Santos, Anderson de Souza (2021)
This dissertation reports results of a study on the potential of the GeoGebra Classroom virtual environment for learning the concept of function and for the development of algebraic thinking. In this study, the prior knowledge of students (14-15 years old) of elementary school about the topic in question was considered, both about the concept of function and about the main functionalities of the GeoGebra software. The actions concerning this research were formulated with the intention of answering the following guiding question: how could the GeoGebra dynamic geometry software favor the learning of the function concepts as develop of algebraic thinking? For that, a pedagogical approach was adopted using problem situations elaborated from the multimedia resources of Classroom version. The investigation was lead according to three aspects: (a) use of the GeoGebra Classroom virtual environment; (b) appropriation of specific curriculum guidelines for learning the concept of function, as proposed by the National Common Curriculum Base (BNCC); and (c) the contextualization of problem situations from the reality of the students themselves. Two didactic proposals were built and analyzed based on different themes: the conscientious consumption of water and the treatment of solid waste. These didactic proposals are part of the educational product developed as part of the research work, whose title “Applications of GeoGebra Classroom in teaching and learning the concept of functions.” reflects our intention to guide the preparation of didactic proposals from this platform. The research was carried out completely remotely, with eleven students from a private school in the municipality of Monte Alegre de Minas. The same teaching resources used by the co-participating institution where the research took place were adopted in the investigation, the Meet and Classroom platforms, belonging, respectively, to Google and GeoGebra online. Based on the concept of function and the use of GeoGebra software, the qualitative analysis of the data built for this research provided us with indications about possible pedagogical approaches to be adapted to the curricular guidelines proposed by the BNCC. The potential of GeoGebra for contextualized learning of the concept of function and for the development of algebraic thinking by students from the 9th grade of elementary school is discussed.